Human telomerase reverse transcriptase expression in colorectal tumors: correlations with immunohistochemical expression and clinicopathologic features - Simsek, Bengu Cobanoglu; Pehlivan, Sultan; Karaoglu, Aziz (Elsevier Science Inc, 2010)
Human telomerase reverse transcriptase (hTERT) proteins in colorectal cancer investigated in several studies, but to our knowledge, hTERT expression has not been evaluated in all of colorectal tumors, including hyperplastic polyps (HPs), adenomas, and carcinomas, on paraffin-embedded tissue sections. The aim of the present study is to investigate immunohistochemical hTERT expression and its relationship with the clinicopathologic features in a spectrum of colorectal tumors. In this study, hTERT expression was determined in HP (n = 20), adenomatous polyp (AP) (n = 20), colorectal adenocarcinomas (n = 20), and normal mucosa (n = 20) by immunohistochemical method. The findings were correlated with the clinicopathologic features. The staining level of hTERT in adenomas and carcinomas was significantly higher than in normal tissues (P < .05). There was also significant difference between HP and AP (P < .05). Level of hTERT in carcinomas was higher than in adenomas, but the difference was of no statistical significance (P > .05). There was no significant association of hTERT expression in cancerous, precancerous, or normal mucosa related to clinicopathologic parameters including age, sex, and size of lesion, (P > .05), but only association with histologic grade for carcinoma was found (P < .05). Levels of hTERT by immunohistochemistry demonstrated that the expression of hTERT was very little in normal mucosa and HP, moderate in AP, and highest in carcinoma. Thereby, hTERT expression may use the aggressiveness of the colorectal tumors as a marker, but it is not related to clinicopathologic data. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: hTERT; Immunohistochemistry; Colorectal tumors; Clinicopathologic features